Effect of Single and Combined Herbicides in Compost on Growth of Sensitive Crops: Green Bean, Cucumber, and Tomato. (15th December 2017) - Chang, R. X.; Michel, F. C.; Gan, J. J.; Wang, Q.; Wang, Z. Z.; Li, Y. M.
ABSTRACT: Compost is frequently used in vegetable production in China, however the feedstocks used for these composts come from a variety of sources, some of which could contain herbicide residues. To evaluate the risk of herbicides on compost products used as growth substrates, we chose three sensitive vegetable crops: green bean, tomato, and cucumber, and grew them in compost without herbicide (CK), with Clopyralid (C1, 0.001 μg/g), Trifluralin (C2, 0.05 μg/g), Imprelis (C3, 0.01 μg/g), and mixed-herbicides (CM). In the CM treatment, all of the herbicides were added at 1/10 the concentration of the single treatments. The media were amended with the composts at 0, 5, 10, and 20%. Emergence rate, Seedling Vigor Index (SVI) and various growth indexes (shoot height, stem diameter, leaf area, root dry weight, and plant biomass) were determined after 45 days. The results indicated that: compost without herbicides (CK) had a positive influence on plant emergence (except green bean), VSI, and growth. The influence increased with each addition up to 20%. Contaminated composts significantly reduced the emergence rate of tomato and cucumber, especially cucumber; the VSI of tomato and cucumber, especially for tomato; and some of the grown indexes of the three crops. The inhibition was more obvious for tomato and cucumber than for green bean. The inhibition of growth index was greater in CM-20 than the other treatments, even though lower concentrations of each herbicide were used. Compost containing Trifluralin had the most inhibitory effect among the three single herbicides. However, the inhibitory effects varied in the different treatments. In conclusion, compost can increase the emergence rate and plant growth index (shoot height, stem diameter, leaf area, root dry weight, and plant biomass), but composts polluted by herbicides had negative impacts on plant growth, especially at higher compost amendment ratios of 20%. Therefore, the utilization of compost made from agricultural wastes, especially in vegetable fields, should be closely monitored.